THE EFFECTIVENESS OF PRASTERONE VS PLACEBO THERAPY AS THE VULVOVAGINAL ATROPHY TREATMENT IN MENOPAUSAL WOMEN: META-ANALYSIS STUDY - Zettira Maulida Prasha; Hari Paraton (UNUSA Press, 2020)
Background : Vulvovaginal atrophy is a condition that often occurs in menopausal women due to Estrogen decreased. Prasterone (DHEA) is a steroid hormone that can be converted into Estrogen in the target tissue. Objective : This paper aims to evaluate the effectiveness of administering Prasterone as Vulvovaginal Atrophy therapy in menopausal women. Methods : A systematic data search was performed on a medical database (PUBMED, Google scholar, Cochrane). Inclusion criteria: (1) randomized study of Prasterone as Vulvovaginal Atrophy therapy in postmenopausal women, (2) all-inclusive papers can be accessed completely, and (3) the data obtained can be accurately analysed. Results: Three RCTs with a total of 696 patients were analysed. The average number of Superficial Cells (mean difference [MD] 7.63, and 95% [CI] 7.57 to 7.70 (P <0.00001). The average number of Parabasal Cells (mean difference [MD] -29.84, and 95% [CI] -30.25 to -29.44 (P <0.00001). The average number of vaginal pH (mean difference [MD] -0.69, and 95% [CI] -0.70 to -0.68 (P <0.00001). The average number of Dyspareunia (mean difference [MD] -0.38, and 95% [CI] -0.39 to -0.37 (P <0.00001). All diamonds do not intersect the vertical line, and have p <0.05, it proves that there are significant differences between the two groups. All non-hysterectomized women have an atrophic or inactive endometrium. Side effects that are often complained of is headache and application site discharge. Conclusion This meta-analysis concludes that Prasterone therapy has a significant therapeutic effect for Vulvovaginal Atrophy in menopausal women